Pengaruh Variasi Latihan Tri Angle dalam Meningkatkan Akurasi Passing Menggunakan Kaki Bagian Dalam pada Permainan Futsal Siswa Ekstrakurikuler - Daniel Parulian Silaban; Ramadan Ginting; Alan Alfiansyah Putra Karo karo; Dewi Maya Sari (Universitas Negeri Medan, 2026)
The study aims to apply variations of exercises that are easy to understand and do, namely variations of Tri Angle passing exercises. The purpose of this study is to determine how the influence of Tri Angle exercise variations in improving the accuracy of Passing Using the Inside of the Foot in Futsal Games for extracurricular students of SMP HKBP Sei Mati Medan on passing results. This type of research is quantitative research with the population and sample of research, namely 12 students of SMP HKBP Sei Mati Medan futsal extracurricular students, where in this study using experimental methods and research design using